Productivity Evaluation of Excavators and Dump Trucks in the Cendana Seam U Pit, PT. Bhumi Rantau Energi, South Kalimantan Province - Singal, Nahbhilah Ken Hapsari; Supandi,; Mukarom, Faisol (ReTII, 2023)
In production operations at PT. Bhumi Rantau Energi, the equipment used in coal getting activities include: 1 Komatsu PC 400 LC-7 digger excavator with a productivity of 165.71 BCM/hour and 11 Hino FM 260 JD dump truck hauler with a productivity of 11.04 BCM/hour O'clock are used in coal-getting activities. The reality in the field is that the productivity of each tool is not maximized due to several factors, one of which is that working time is not used optimally, which affects the EU (Effective Utilization) values of 59% and 54%, which do not meet the expected values. Therefore, an evaluation of the factors that affect productivity was carried out using the Quality Control Circle method, which was then carried out to Improve EU, which was previously low, then increased to 65% and 60% so that the productivity of the digger equipment increased by 182,14 BCM/hour and the productivity of the means of hauler was 12,14 BCM/hour by increasing the number of means of hauler so that the digger equipment and the means of hauler are in harmony. Efforts to increase the work efficiency of tools with good time management and supervision This is done in order to avoid the productivity of the tool not working properly, or it can be said that the tool is not working as it should because time cannot be used properly.